Organizational Climate and Teachers Characteristics as Predictors of Secondary Schools’ Productivity - Agbajeola, R. O. (NIU Journal of Social Sciences, 2019)
The productivity of secondary schools has come under attack over time as been under productive. The study investigated the extent to which organizational climate and teachers’ characteristics predict secondary school productivity in Ogun State. The Study adopted descriptive survey design with population comprising of 675 teachers in public senior secondary school in Ijebu division of Ogun State. While simple random sampling technique was used to select 148 subject teachers.  Four (4) validated research instruments were used for this study which are Organizational Climate Survey Questionnaire (OCSQ, α=0.75), Teachers’ Information Questionnaire (TIQ), Sports Productivity Rating Scale (SPRC, α= 0.74) and Socio-cultural Productivity Rating Scale (SCRRS,α=0.71) as measures of  School Productivity Questionnaire (SPQ). The result of the study revealed Organizational Climate and Teachers’ Characteristics jointly predicts secondary school productivity (F = 42.274, P < .05). It also shows that independently, teacher characteristics and organizational Climate significantly predicts secondary school productivity in Ogun State.  The study concludes that school productivity can be influenced by both organizational climate and Teacher characteristics in secondary schools and also recommends that teachers should be valued and motivated. Keywords : Teachers; School productivity; Organizational Climate; Teacher Characteristics.